Dari Kearifan Lokal Menuju Pasar Global : Memanfaatkan Strategi Bisnis Berbasis Warisan Budaya untuk Pertumbuhan UMKM di Banyumas - Puspita Lianti Putri; Riska Nadiya Salsabela (BADAN PENERBIT STIEPARI PRESS, 2025)
This study explores how Micro, Small, and Medium Enterprises (MSMEs) in Banyumas utilize local wisdom as a business strategy to increase competitiveness in national and global markets. Using a qualitative case study approach, data were obtained through in-depth interviews, participant observation, and document review involving MSMEs with locally based cultural products. Thematic analysis identified four key themes highly relevant to MSME development: preservation and innovation of culturally based products, branding strategies through storytelling, digitalization for market expansion, and barriers to global marketing. This study demonstrates that integrating local culture can strengthen brand identity and provide additional appeal to consumers seeking authenticity and cultural value in products. Products such as batik, handicrafts, and Banyumas specialty foods can appeal to the global market if well-packaged and accompanied by stories that touch on cultural values. However, limited digital literacy and export regulations are significant obstacles to MSME market expansion globally. Therefore, stronger support from the government and the academic sector is needed to help MSMEs improve their understanding of digital marketing, improve export regulations, and create international networks. Synergy between MSMEs, the government, and academics is essential to design integrated strategies based on culture and technology to expand their market reach. This research contributes theoretically to the creative economy literature and provides practical guidance for the sustainable development of culture-based MSMEs, which can ultimately improve the competitiveness and welfare of MSMEs in Banyumas. Furthermore, this research also highlights the importance of utilizing digital technology as an integral part of MSME business strategies.